Ethical champions, emotions, framing, and team ethical decision making - Chen, Anjier; Treviño, Linda Klebe; Humphrey, Stephen E (Journal of applied psychology, 2020)
Research has offered a pessimistic (although limited) view regarding the effectiveness of ethical champions in teams and the social consequences they are likely to experience. To challenge this view, we conducted two multimethod (quantitative/qualitative) experimental studies in the context of entrepreneurial team decision-making to examine whether and how an ethical champion can shape team decision ethicality and whether ethical champions experience interpersonal costs. In Study 1, we found that confederate ethical champions influenced team decisions to be more ethical by increasing team ethical awareness. Focusing on the emotional expressions of ethical champions, we found that sympathetic and angry ethical champions both increased team decision ethicality but that angry ethical champions were more disliked. Analysis of team interaction videos further revealed moral disengagement in team discussions and the emergence of nonconfederate ethical champions who used business frames to argue for the ethical decision. Those emergent phenomena shifted our focus, in Study 2, to how ethical champions framed the issues and the mediating processes involved. We found that ethical champions using ethical frames not only increased team ethical awareness but also consequently reduced team moral disengagement, resulting in more ethical team decisions. Ethical champions using business frames also improved team decision ethicality, but by increasing the perceived business utility of the ethical decision. (PsycINFO Database Record (c) 2020 APA, all rights reserved).